Enhancing the Adoption of Financial Innovations to Foster Socioeconomic Welfare - Tamar Gamsakhurdia; Lamara Kadagidze (European Scientific Journal, ESJ, 2024)
The integration of digital technologies has garnered global attention, with a primary focus on their potential to streamline the convergence of digital and non-digital economies. This trend is poised to generate self-employment opportunities and spur socio-economic development, transcending geographic boundaries. In the context of Georgia, where the number of digitally connected individuals is on the rise, it becomes imperative to ascertain the extent to which financial technologies deployed in the financial services industry contribute to the well-being of the population and business representatives. This research aims to assess the benefits of these technologies while acknowledging that their utilization does not impede the future implementation of novel financial innovations by institutions in the sector. While including both, qualitative and quantitative analysis, the study examines the significance of financial technologies in the country's economy in terms of financial resources and the impact on the well-being and growth of the population and companies. Emphasizing user-centricity, it underscores the need to prioritize the fulfillment of users' requirements. Notably, it is not solely traditional financial institutions that shape the landscape, but also technology firms offering innovative products and services, which exert a critical influence on fostering a dynamic business environment. Furthermore, the evaluation of emerging technologies such as cloud computing, the Internet of Things (IoT), artificial intelligence, and blockchain elucidates their potential impact in enhancing the well-being of businesses and the general population. Nevertheless, given the current stage of their development, a comprehensive nationwide implementation of these technologies remains challenging.